2018
DOI: 10.1097/md.0000000000010729
|View full text |Cite
|
Sign up to set email alerts
|

Potential common factors associated with predisposition to common cold in middle-aged and elderly Japanese

Abstract: People worldwide frequently catch a common cold, which occasionally develops into secondary severe conditions such as pneumonia. However, it is unclear whether predisposition to the common cold is associated with the individual's characteristics including age, body weight, lifestyles, diets, and intestinal functions, besides exposure to a responsible pathogen. We addressed this issue epidemiologically considering many relevant clinical factors.We reviewed data from a cross-sectional study consisting of 39,524 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The positive effects of exercise for general mental and physical health as well as for specific physiological functions including the immune system have been demonstrated in several systematic reviews and meta-analyses (18). Lack of exercise is one of the most common causes of chronic diseases, making patients more susceptible to infections and complicating disease courses (104,105). Evidence on preventive effects of exercise for the elderly is overwhelmingly positive (106).…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects of exercise for general mental and physical health as well as for specific physiological functions including the immune system have been demonstrated in several systematic reviews and meta-analyses (18). Lack of exercise is one of the most common causes of chronic diseases, making patients more susceptible to infections and complicating disease courses (104,105). Evidence on preventive effects of exercise for the elderly is overwhelmingly positive (106).…”
Section: Exercisementioning
confidence: 99%
“…Sleep deficiency, poor sleep quality or shifts in the chronobiologic sleep rhythm are associated with an increase in chronic diseases (123). Insufficient sleep (<7 h) is also associated with a significant increase in upper respiratory tract infections (105,124,125). CIM offers a variety of ways to improve sleep duration and quality including the application of oil mixtures of aromatherapy (126), e.g., lavender, but also MBSR, yoga, and tai chi may improve sleep quality (127).…”
Section: Sleepmentioning
confidence: 99%
“…Previous research has indicated that chronic insomnia is one of the causes of common cold or pneumonia. [1][2][3][4] According to previous studies, 5 impaired overall health may affect insomnia. Research indicates that narcolepsy frequently accompanies influenza, 6 suggesting the possibility that influenza influences sleep behaviors.…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…There are two possibilities regarding the relationship between impaired overall health and insomnia: Insomnia contributes to the occurrence of impaired overall health, or impaired overall health leads to insomnia. Previous research has indicated that chronic insomnia is one of the causes of common cold or pneumonia . According to previous studies, impaired overall health may affect insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…The common cold is a disease of diverse aetiology (see Appendix 3) (Heikkinen 2003). Premature babies, children, the elderly, and other populations with comorbidities such as chronic lung diseases (chronic obstructive pulmonary disease), congenital heart disease, and asthma are more prone to viral infections that cause the common cold, including respiratory syncytial virus (RSV), human rhinovirus (HRV), parainfluenza, coronavirus, and adenovirus (nonpolio) (Johnston 2017;Lu 2020;Rubner 2017;Shibata 2018). Additionally, in humans, coronavirus such as the HCoV-229E, HCoV-OC43, HCoV-NL63, and HCoV-HKU1 strains are responsible for URT infections (URTI) associated with the common cold (Zumla 2016).…”
Section: B a C K G R O U N D Description Of The Conditionmentioning
confidence: 99%